Performance Test of Hotong Seed Billing Machine (Setaria italica (L.) P. Beauv) Abrasive Roll Type with Grinding Stone - Sutejo, Agus; Abdillah, Kemas Asror; Sucahyo, Lilis; Wicaksono, Dionisius Dwi; Pramuhadi, Gatot (Jurnal Agricultural Biosystem Engineering, 2023)
Indonesia has a lot of diversity, one of which is in food. Carbohydrates are basic food needs that must be met, in Indonesia there is the potential for various alternative foods. One of the alternative food ingredients producing carbohydrates is hotong. Hotong is a plant that is often found in Indonesia but has post-harvest constraints, namely in the sowing process. Therefore, research was conducted to determine the performance of an abrasive roll type grinding machine with the characteristics of hotong seeds. The research was conducted at PT. Daud Teknik Maju Pratama in November 2022. The treatment of hotong seeds that are sprayed as many as three passes with various levels of rpm speed, namely 806, 940, and 1128 rpm and carried out three repetitions at each rpm. The performance test results of the crushing machine showed the highest scattered capacity and shrinkage at a rotating speed of 1128 rpm, the highest yield and effectiveness of skin separation at a speed of 806 rpm, while at the highest polishing quality at a speed of 940 rpm. Rotating speed affects the sowing results, the faster the engine rotation speed, the quality and capacity of the sowing will increase. In addition, the tilt angle of the machine also affects the result of the sowing capacity. The terminal velocity value is influenced by the weight of the hotong seeds, the higher the weight on the sample, the higher the terminal velocity value obtained. Keywords:  Abrasive Roll, Hotong, Polisher.